(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides information about the process of formation of the Uzbek language, the period and stages of development, and the role of languages of other systems in the formation of the Uzbek literary language.